Adapting roughages varying in quality and curing processes to the nutrition of beef cattle: Prairie hay vs. corn cobs; A special supplement vs. milo grain and soybean meal. - Smith, E.F.; Richardson, D.; Baker, F.H.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Forty choice-quality Hereford heifers were divided as equally as possible into four lots of 10 animals each. The heifers originated in Barber county, Kansas. The rations used are shown in Table 53. An attempt was made to equalize the protein and total digestible nutrient intake between the lots receiving prairie hay and lots receiving corn cobs as roughages. The animals receiving corn cobs were given 50,000 International Units of vitamin A per head daily. The 3 pounds of special supplement fed daily to Lot 7 was composed of 2.25 pounds soybean meal, 0.50 pound molasses, 0.18 pound steamed bone meal, 0.06 pound salt, and 0.01 pound vitamin supplement (2,250 International units of vitamin A and 400 International Units of vitamin D per gram). A mineral mixture of 1 part salt and 2 parts steamed bone meal and salt were fed free choice. Water was available at all times.
Keywords: Beef; Roughage; Curing process; Vitamin A; Gain